Persistent lower paraplegia due to decompression illness in a fisherman using a compressor for diving - Grantika Nugraha; Muhammad Arismunandar (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2026)
Decompression illness (DCI) is a term that encompasses injuries resulting from arterial gas embolism (AGE) and decompression sickness (DCS). It produces symptoms that range from mild musculoskeletal pain to severe neurological involvement. We report the case of a 32-year-old man who developed progressive lower limb weakness, sensory loss below T10, and bowel–bladder dysfunction shortly after a 20-minute compressor-assisted dive. Neurological examination revealed inferior paraplegia with hypoesthesia below the T10 level. MRI showed an intermedullary lesion with spinal cord edema between T8 and T11, consistent with spinal DCI. The patient underwent three sessions of recompression therapy at a secondary hospital without motor improvement and was subsequently referred to a tertiary center. After nine days of hospitalization, partial improvement was observed, though paraplegia persisted. This case highlights the challenges of managing DCI in settings with limited hyperbaric access and emphasizes the importance of early recognition, immediate recompression, and timely referral to improve neurological outcomes and reduce long-term disability in divers.